The Impact of Fiscal and Monetary Policies on The Growth of The Electric Vehicle Population in Indonesia - Siregar, Willy Novananda; Milasari, Mimin; Viasco, David Candra; Aritonang, Julius Dermawan; Kunto, Retiono (Dinasti International Journal of Digital Business Management, 2024)
This study aims to determine the impact of fixed and monetary policies on the growth of the electric vehicle population in Indonesia. The method used in this study is qualitative with a literature review approach. The data analysis technique used in this study is critical analysis. The results of the study show that electric vehicle (EV) production is a top priority, as well as the development of supporting infrastructure regulated in the 2020-2024 National Medium-Term Development Plan (RPJMN). One of the impacts that has occurred on the electric vehicle industry is the provision of special incentives for battery-based electric cars. The form of incentives for consumers includes providing a 0% tax on the Luxury Goods Value Added Tax (PPnBM).